Exploring Coaching Leadership Behaviours in Strength and Conditioning Coaching: Preferences of NCAA Division I and II Collegiate Student-Athletes Based on Task Dependence - Severiano Tiberi; Joseph I. Esformes; George Jennings; Steve Cooper; Jeremy Moody (Journal of Coaching and Sports Science, 2024)
To explore collegiate student-athletes? preferences of coaching leadership behaviours in strength and conditioning (SnC) coaching and evaluate differences between the preferences of coaching leadership behaviours based on task dependence. Method a total of 145 National Collegiate Athletic Association student-athletes (independent sports athletes = 48, interdependent sports athletes = 97), aged 18-25 years, with a mean = 3 (SD = ±1) SnC sessions per week, participated. Participants completed an electronic questionnaire involving the athletes? preference version of the Revised Leadership Scale for SnC. Results summary statistics revealed that the most favoured behaviour was 'training and instruction', median = 4.5 (IQR = 1.0), while the least favoured was ?autocratic?, median = 2.0 (IQR = 0.5). Independent sports athletes preferred training and instruction more (median = 5.0, IQR = 0.6) than interdependent sports athletes (median = 4.5, IQR = 1.0). Interdependent sports athletes preferred social support more (median = 3.5, IQR = 1.0) than independent sports athletes (median = 3.0, IQR = 0.6). The observation of a marginal statistically significant difference for social support suggests task-dependence-based variations (p = 0.018). However, small effect sizes indicate that differences are not practically significant. Conclusion and recommendation: this study presents insights into the preferences of coaching leadership behaviours among student-athletes in SnC coaching. It highlights key behaviours such as training and instruction, positive feedback, situational considerations, and social support. These findings inform coaching practice and provide a foundation for further research into coaching leadership behaviours in SnC coaching.